Monte Carlo simulations and DSP application for optical parameter measurement - Nguyen, Tuan Anh (H. : ĐHQGHN, 2017)
The Texas Instrument TMS320VC55I0 DSK's calculation abilitiy with different program languages is investigated for minimum the DSP's measurement time. The steps of Monte Carlo simulations embedded into the DSK's flash through the DSK's JTAG interface for optical parameters measurement including absorption coefficient7.t,, scattering coefficient F, and anisotropy 8'are presented. The obtained results for diluted milk standard samples are also reported.